Hubungan Enzim Hepar SGOT dan SGPT pada Pasien Diabetes Mellitus Tipe 2 - Dewi, Novita; Supriyadi, Supriyadi (Jurnal Akademika Baiturrahim Jambi, 2024)
Diabetes mellitus is a collection of metabolic symptoms starting with insulin secretion or insulin resistance. Insulin resistance in Type 2 Diabetes Mellitus (T2DM) sufferers causes a decrease in the absorption of glucose levels. The liver cytosol is a source of glucose energy obtained from fatty acid synthesis. This synthesis event causes "fatty liver", namely the accumulation of lipids in the liver, this is very dangerous and in an effort to prevent the severity of this disease it is necessary to check liver enzymes, namely SGPT and SGOT in T2DM sufferers. This study aims to analyse the correlation of liver enzymes SGPT and SGOT in T2DM sufferers. This research has a collative design with an approach to collecting data on variable blood sugar levels and liver enzymes SGOT and SGPT at one time which is called a cross-sectional approach. The total sample was 25 patients taken using purposive sampling technique. The observation sheet is used as an instrument to collect data. This research resulted in the highest number of studies showing 56% of abnormal blood glucose levels with abnormal SGPT liver enzymes. There is no correlation between blood glucose levels and the liver enzyme SGPT in T2DM sufferers with a p-value of 0.54. The highest abnormal blood glucose level is 4% with abnormal SGOT liver enzymes. There is no correlation between blood glucose levels and the liver enzyme SGOT in T2DM sufferers with a p-value of 0.28. The conclusion of the study was that there was no correlation between the liver enzymes SGPT and SGOT in T2DM sufferers.